MODEL HALAQOH SEBAGAI ALTERNATIF PEMBENTUKAN KARAKTER ISLAMI MAHASISWA IAIN BENGKULU - Sepri Yunarman (Institut Agama Islam Negeri Bengkulu, 2017)
Islamic education aims to shape the Islamic character of each individual. Education is sourced from the Qur’an and As-Sunnah. IAIN Bengkulu, as an Islamic university is certainly responsible for giving birth to a generation or scholar of scientific knowledge and noble character. However, in the current reality, one of the vision and mission of IAIN Bengkulu to give birth to academic Persons with Islamic principles can not be reached maximally. This is evidenced by the still large number of IAIN students who are not performing the duties that the religion mandates. Well, in prayer, read the Qur’an, association and so forth. This issue becomes a shared responsibility to overcome them. Therefore, the authors offer the wrong concept of Islamic coaching with halaqoh model, as an alternative to Islamic character building on IAIN Bengkulu